Question and comment for FETKOVICH’s typical curve - CHEN Yuanqian,WANG Xin,LIU Yang,SHI Xiaomin (Youqicang pingjia yu kaifa)
FETKOVICH proposed the water influx rate equation in finite aquifer and the type curve with constant pressure in 1971 and 1980 respectively, which have been widely recognized and cited by experts both domestically and internationally. His methodology allows for the determination of a well's drainage radius and area by fitting actual production data to his type curve, a technique that has gained popularity among field experts. The derivation of this paper shows that the equation for water influx rate equation in finite aquifer of FETKOVICH is an is characterized by an exponential decline, a model he directly applied to analyze production declines in wells with volumetrically closed boundaries. He derived a dimensionless time for the type curve based on the relationship with the initial decline rate and used the inverse of dimensionless pressure as a proxy for dimensionless production to develop the type curve's dimensionless production profile. However, it's important to note that FETKOVICH's model does not establish a direct functional relationship between dimensionless time and dimensionless production in the type curve model, which means that a comprehensive dimensionless type curve cannot be formulated directly from his equations. This article deduces the water influx rate equation in finite aquifer and the dimensionless time and dimensionless production of the type curve, and questioned and commented on the existing problems.